(untitled) (Kronika Bydgoska, 2010)
The book Strzępy wspomnień (Snatches of Memories) by Leszek Jan Malinowski (1925-2010), Vilnius resident by birth and Bydgoszcz resident by choice, allow going into the rich personality of the man, who was freąuently put to the hard test by the changing reality. The war and the Lithuanian, German and Soviet occupation, conspiracy, service in the Home Army, underground operation in the years 1945- 1946, and the Polish post-war reality were engraved in his memory permanently. Some events described by L. Malinowski, e.g. the “Redeploymenf ’ action of the Home Army Vilnius District, are really sensational. Wanted by the Secret Political Police sińce 1946, he luckily escaped arrest and surely the death penalty. He started to use his real personal data only in 1955.In the city on the Brda River, which was gradually becoming his city, he devoted himself to teaching and later academic work. As a non-partisan person “stimulated compulsorily”, he was the deputy superintendent of schools and education for a certain period of time. He combined his pedagogical work with extremely active social operations. Being active in the Polish Teachers’ Union, he organised the NSM “Znicz” Teachers’ Housing Associ- ation in Bydgoszcz and was its first chairman. He was active in the BTN Bydgoszcz Scientific Society and the Friends of Bydgoszcz Association. From 1980, he was active in the Christian Culture Weeks.This Bydgoszcz resident by choice did not forget about his beloved Vilnius and Vilnius Region. When Poland regained sovereignty in 1989, with passion he devoted himself to the work in the Friends of Vilnius and Vilnius Land Association. For 20 years, he was the association’s chairman. The association conducted broad publishing operations. Within “Biblioteka Wileńskich Rozmaitości”, it published almost 100 books. In 1990, L. Malinowski organised the Vilnius-Nowogródek Community of the Word Union of the Home Army Veterans and became its first chairman.The book Strzępy wspomnień has not only literary values but is also an important historical record, for which not only Vilnius and Bydgoszcz resi- dents will be reaching.